2022
DOI: 10.1186/s41182-022-00461-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for wasting among hospitalised children in Nepal

Abstract: Background Malnutrition has various adverse effects in children. This study aimed to determine risk factors for malnutrition among hospitalised children, changes in nutritional status at admission and discharge and effects of use of systematic anthropometric measurement in identification of malnutrition. Methods We enrolled 426 children, aged between 6 months and 15 years, admitted to Siddhi Memorial Hospital, Bhaktapur, Nepal, from November 2016 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Stunting was higher among younger children compared with older children. Our data are higher than regional data (22 %) (6) and another cross-sectional, hospital-based study (19 %) (25) . This may be reflective economic effects of COVID-19 particularly related to the rising cost of food and supply chain restrictions, but may also be reflective of the socio-demographic characteristics of the children served by this hospital.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Stunting was higher among younger children compared with older children. Our data are higher than regional data (22 %) (6) and another cross-sectional, hospital-based study (19 %) (25) . This may be reflective economic effects of COVID-19 particularly related to the rising cost of food and supply chain restrictions, but may also be reflective of the socio-demographic characteristics of the children served by this hospital.…”
Section: Discussioncontrasting
confidence: 85%
“…Compared with national data and other hospital-based surveys, we found a higher prevalence of wasting among our sample (8 % and 9·2 % (on admission) v . 17·3 %, respectively) (6,25) . Several factors may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that 34.4 of the admitted children were severely stunted which is higher than the result of a hospital based studies done in Egypt and Western Kenya which revealed that stunted among under 60 month old children were ly [23,24]. More than thirty percent of severely stunted children belonged to the age group 06-24 months which is much higher than the frequency of stunting among 06-24 month old children in a study included hospitalized children in Nepal (4.7%) and a community based study done in Vellore, India (14.1%) [25,26]. Stunting by the age of 2 years is largely irreversible, as the child cannot recover height in the same way that they can regain weight [9,10].…”
Section: Discussionmentioning
confidence: 99%